PENGARUH PERTUMBUHAN PENJUALAN, LABA PER SAHAM, DAN TOTAL ARUS KAS TERHADAP HARGA SAHAM PADA PERUSAHAAN YANG TERDAFTAR DI JAKARTA ISLAMIC INDEX - Ajrina, Ajrina; Safaruddin, Safaruddin; Mizan, Mizan (Politeknik Negeri Lhokseumawe, 2024)
Abstract: This study aims to determine the effect of sales growth, earnings per share, and total cash flow on stock prices in companies listed in the Jakarta Islamic Index. The population in this study is 42 companies registered in the Jakarta Islamic Index. The sampling technique using Purposive Sampling is the selection of sample data based on certain criteria obtained as many as 30 observations with 10 companies within a period of 3 years. This study uses a quantitative approach. The data analysis technique uses multiple linear regression analysis. The statistical analysis tests used were classical assumption tests in the form of normality, multicollinearity, heterokedasticity, and autocorrelation tests and determination coefficient tests, as well as hypothesis tests both F tests and t tests. The determination coefficient test shows that the ability to grow sales, earnings per share, and total cash flow affects the stock price by 76.8%. The results of the study show that simultaneously sales growth, earnings per share, and total cash flow have a significant effect on the stock price of companies listed in the Jakarta Islamic Index. Meanwhile, partially sales growth has a negative and cynical effect on the stock price. Earnings per share partially have a positive and negative effect on the stock price. Total cash flow partially does not have a significant effect on the stock price. Keywords: Sales Growth, Earnings Per Share, Total Cash Flow, Stock Price